Os impactos das ações extensionistas do Projeto Leme: oficinas preparatórias para o ENEM aos estudantes do município de São Borja-RS - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The present paper sought, through documental research and semi-structured interviews, to analyze the impacts of the University Extension Project LEME: Preparatory Workshops for the ENEM to the students of the municipality of São Borja-RS. Starting with a brief discussion about the emergence of Higher Education Institutes in the country and its federalization, followed by the institutionalization of the Extension as a fundamental pillar for the formation of professionals aware of theirs and the universities role socialwise in the country, it is sought to reflect on how this process of construction of Higher Education in Brazil was directed at the great elites of the country and, through public policies of access democratization to Higher Education, this reality began to change. Based on that, the Federal University of Pampa presented itself as a result of these policies, and the Licentiate degree course in Human Sciences at the São Borja-RS campus was an attempt to overcome the deficiency of teachers graduated in the area in the public schools of the region. As an initiative of the course students, the emergence of the Project LEME: Preparatory Workshops for the ENEM presents itself with the objective of promoting the preparation, without any cost, of students and workers of the municipality of São Borja who seek to enter higher education. Thus, according to the methodologies adopted for the present research, it was possible to trace the profile of students who attended the editions of 2015, 2016, 2017 and 2018, observing that most of these students come from the northern region of the municipality, the same region where the University is inserted, and are of the female public. Regarding income, it was observed that the predominant public is classified, by the Federal Government, with a "Vulnerable" or "Lower Middle Class" socioeconomic profile, fomenting the discussion about the distance of poor students from the university space. In addition, the research indicates the approval rating of students in Higher Education Institutions (public and private) and from this, it was sought to reflect on the importance of extension activities, especially the LEME project, to the community and students who participated.
Keywords: Ensino superior; Extensão Universitária; Brasil; Política pública; Higher education; University Extension; Public policy; CNPQ::CIENCIAS HUMANAS